EXAMINING THE DISCOURSE ANALYSIS ON THE SONG LYRIC ENTITLED “HEAL THE WORLD” BY MICHAEL JACKSON - Willy Cardo Hutajulu; Oscar Pardomuan Butarbutar; Jeremia Situmorang; Silvia Torong; Vistan Sebasty Situmeang; Herman Herman (Jurnal Scientia, 2023)
This library research aimed at finding the three aspects of discourse analysis: contextual, grammatical, and lexical aspects of Michael Jackson’s song lyrics entitled “Heal The World”. After analysis, it can be found that the life experience and background of the songwriter and singer are closely related to the idea proposed within the song lyrics. Whereas, the result of the grammatical and lexical analysis gives a depiction of cohesion and coherence of the song discourse of “Heal The World “.the first element we see in lines (79), (80), (81), (82), (83), (84), (85), (86), (87), (88), and (89) is the first plural personal pronoun reference. There is the pronoun "you" refers to all people in this world who believe that everyone should heal this world we live in for the sake of our children in the future. The second personal reference here is also the pronoun "me" in the line is the singular personal object pronoun that refers to the singer that also must heal the world to make it a better place for the human being. And there are 26 forms of a conjunction of "and", 49 forms of a conjunction of "for", 3 forms of a conjunction of "so", and 1 form of a conjunction of "or".On the other side, it is very easy to find lexical aspects of the lyrics of this song. There are several forms of repeating the sentence "Heal The World" eleven times to influence listeners and supporters as well as opponents of the idea brought by the singer/writer that everyone must contribute to creating peace.